2022
DOI: 10.3389/fpubh.2021.801035
|View full text |Cite
|
Sign up to set email alerts
|

Profile and Predictors of Maternal Quality of Life During Physiological Pregnancy: A Cross-Sectional Analysis

Abstract: BackgroundQuality of Life (QoL) and its determinants are significant in all stages of life, including pregnancy. The physical and emotional changes during pregnancy affect the QoL of pregnant women, affecting both maternal and infant health. Hence, assessing the QoL of pregnant women is gaining interest in literature. We, therefore, aimed to describe the QoL of pregnant women during physiological pregnancy and to identify its associated predictors in women attending a public healthcare institute of Quetta city… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 31 publications
(39 reference statements)
0
3
0
1
Order By: Relevance
“…This has been confirmed by a study ( 25 ), showing that pregnant women with higher education were more affected by low self-esteem. On the contrary, another study ( 17 ) has concluded that the more educated women were, the more satisfied they were with their quality of life.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This has been confirmed by a study ( 25 ), showing that pregnant women with higher education were more affected by low self-esteem. On the contrary, another study ( 17 ) has concluded that the more educated women were, the more satisfied they were with their quality of life.…”
Section: Discussionmentioning
confidence: 95%
“…Other predictors such as age, trimester, parity, pregnancy planning ( 17 , 26 ), partnership ( 3 ) have also been found to be related to quality of life. These, however, were not statistically significant in our study.…”
Section: Discussionmentioning
confidence: 99%
“… 6 , 13 However, in Slovac Republic, Pakistan, and Greece the HRQoL during pregnancy has proven to be good and excellent. 14 , 15 , 16…”
Section: Discussionmentioning
confidence: 99%
“…Kekhawatiran dan stresor wanita hamil akan bervariasi dengan faktor penentu yang berbeda-beda pula. Kajian profil dan predisposisi kualitas hidup wanita hamil yang dilakukan oleh Ishaq et al (2022) memberikan penjelasan bahwa usia, riwayat pendidikan formal, pekerjaan, pendapatan, status pernikahan, dan trimester kehamilan adalah karakteristik demografi predisposisi kualitas hidup. Hasil penelitian ini memperlihatkan bahwa status pekerjaan, riwayat pendidikan formal, dan status ekonomi berhubungan secara statistik dengan kualitas hidup wanita hamil dengan kehamilan risiko tinggi.…”
Section: Pembahasanunclassified